Seasonal fluctuations in airway responsiveness in elite endurance athletes - Hemingson, H. B.; Davis, B. E.; Cockcroft, D. W. (Canadian Respiratory Journal, 2004)
BACKGROUND: It has been suggested that exposure to winter training conditions (irritants in indoor facilities and/or cold, dry air in the outdoors) can increase airway responsiveness in elite endurance athletes. OBJECTIVES: It has yet to be elucidated whether elite endurance athletes experience seasonal fluctuations in their airway responsiveness. METHODS: Eighteen members of a varsity cross-country running team underwent screening procedures and five members were enrolled in the study. Each athlete completed a respiratory and training questionnaire, and underwent allergy skin prick testing. Airway responsiveness was evaluated using a methacholine challenge on four occasions. RESULTS: The participants demonstrated a significant (more than twofold) increase in airway responsiveness (P=0.0496) during the first winter evaluation compared with the autumn baseline. The second winter evaluation still showed an increase but it was not statistically significant. Airway responsiveness had returned to baseline (autumn) values at spring testing.CONCLUSION: Elite endurance athletes experience seasonal fluctuations in airway responsiveness. The specific stimuli that cause this are unknown, but it is speculated to be due to exposure to cold, dry air and/or inhaled irritants that may be present in indoor training facilities.